PERTUMBUHAN BIBIT KOPI ROBUSTA TERHADAP PEMBERIAN EKSTRAK REBUNG DAN PUPUK ORGANIK AZOLLA - Harahap, Ariani Syahfitri; Siagian, Marintan (PLANTKLOPEDIA: Jurnal Sains dan Teknologi Pertanian, 2022)
This study aims to determine the effect of giving bamboo shoot extract and organic fertilizer azolla and its interaction on the growth of robusta coffee (Coffea robusta L.) seedlings. The design used in this study was a factorial randomized block design (RBD) with 2 factors with 16 treatment combinations and 2 replications in order to obtain a total of 32 plots of research treatment plots. The results showed that bamboo shoot extracts and the application of Azolla organic fertilizer and their interactions did not affect all observation parameters such as plant height (cm), number of leaves (strands), stem diameter (mm), plant wet weight (grams), and dry weight. plant (grams). Where the best bamboo shoot extracts in this study were found in R2 treatment (200 g / plot). The best application of azolla organic fertilizer in this study was found in treatment A2 (10 g / plot). Keywords: Growth, Coffee, Extract, Bamboo shoots, Azolla